2016
DOI: 10.4012/dmj.2016-055
|View full text |Cite
|
Sign up to set email alerts
|

Influence of eccentric cyclic loading on implant components: Comparison between external joint system and internal joint system

Abstract: The purpose of this in vitro study was to investigate the influence of eccentric loading on implant components by measuring screw loosening and observing these components under several load positions and magnitudes. The external and internal joint system implants with butt joint connection were subjected to cyclic loading tests according to the specifications of ISO 14801. Load position was set at 0, 4, or 8 mm, and load was set at 100 or 300 N. On the external joint system, the reverse torque values decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 18 publications
(33 reference statements)
1
16
0
2
Order By: Relevance
“…Hence, Gr NS(I) could pass the cyclic test in the current study, but Gr NS(NI) could not. The surface analysis of the abutments through SEM indicated burnishing on the octagonal corners, revealing that the index could provide resistance to the torsional moment, similar to the findings of Katsuta and Watanabe (), Sakamoto et al (), and Yao et al (, ). Therefore, the index design is crucial for achieving stable connections because it provides antitorsion (Khraisat, Hashimoto, Nomura, & Miyakawa, ; Yao et al, ).…”
Section: Discussionsupporting
confidence: 83%
“…Hence, Gr NS(I) could pass the cyclic test in the current study, but Gr NS(NI) could not. The surface analysis of the abutments through SEM indicated burnishing on the octagonal corners, revealing that the index could provide resistance to the torsional moment, similar to the findings of Katsuta and Watanabe (), Sakamoto et al (), and Yao et al (, ). Therefore, the index design is crucial for achieving stable connections because it provides antitorsion (Khraisat, Hashimoto, Nomura, & Miyakawa, ; Yao et al, ).…”
Section: Discussionsupporting
confidence: 83%
“…There are several studies supporting the superior mechanical stability of the internal connection compared to external More specifically, in certain studies it was found that screw loosening was more often in external connection implants compared to internal connection . The problem is often encountered in external hexagon implants during the first 2 years from the placement of the prosthetic restoration, while specific reference is made regarding the screw loosening in single external hexagon implants than in similar implants with internal connection .…”
Section: Discussionmentioning
confidence: 99%
“…The external hexagon has been in use for decades and has been incorporated in several competing systems. It shows certain disadvantages because of its small height There are several studies supporting the superior mechanical stability of the internal connection compared to external [27][28][29][30] More specifically, in certain studies it was found that screw loosening was more tion. 3,7,24,31,32 The problem is often encountered in external hexagon implants during the first 2 years from the placement of the prosthetic restoration, 22 while specific reference is made regarding the screw loosening in single external hexagon implants than in similar implants with internal connection.…”
Section: Internal or External Connection Of Implant-abutmentmentioning
confidence: 99%
“…The internal connection is reported to have advantages over external connection in the stability of the implant-abutment connection and has better resistance of torque loss and screw loosening. [54][55][56][57][58][59] According to a recent systematic review of Vetromilla et al, 60 abutment screw loosening and abutment fracture occurred more often in external hexagon connection comparing to internal hexagon or Morse taper connections in clinical studies. There are also studies stating that the difference in connection types does not have a significant influence on screw loosening.…”
Section: Types Of Implant-abutment Connectionmentioning
confidence: 99%